Editorial, Siddhajyoti Interdisciplinary Journal 2024 - Ghimire, Nani Babu (Siddhajyoti Interdisciplinary Journal, 2024)
In the fifth volume of Siddhajyoti Interdisciplinary Journal (SIJ), we present 13 carefully curated articles that have undergone a rigorous peer-review and editing process. This volume showcases the work of emerging scholars in Nepal, spanning diverse fields such as English, Nepali, Linguistics, Social Studies, Healthe education and Science education. We are confident that the insights shared in these articles will prove valuable to future generations of multidisciplinary practitioners in Nepal. In this volume, Bal Ram Adhikari and Kumar Narayan Shrestha have examined the challenges faced by university teachers when instructing B. Ed. English major students in reading. Binod Kumar Yadav has analyzed causativized syntactic complex predicates in southern Saptarian Maithili within the framework of Lexical Functional Grammar (LFG). Khem Raj Rauteda has aimed to explore teachers' ideologies concerning the use of English as a Medium of Instruction (EMI) in non-English subjects. Lokendra Oli has addressed issues hindering professionalism in protecting service users in his article. Mahendra Kumar Budhathoki has investigated the representation of sexist, abusive, and ingrained prejudices and hatred against women in Nepali Proverbs. Rajeshwer Prasad Yadav has described the current situation of using ICT tools for online teaching by science education teachers at higher levels in both constituent and affiliated campuses in Madhesh Province, Nepal. Ram Chandra Dahal aims to investigate knowledge and perceptions of adolensent girls on HIV/AIDS in Nepali context. Rom Nath Sharma has explored teachers' practices of English Language Teaching (ELT) in a cross-cultural context. Uma Nath Sharma has shared his personal experience in refining EndNote's default in-text citations across various reference types to achieve accurate in-text citations in adherence to the American Psychological Association (APA) style. कमला रेग्मी र टीकादेवी पोख्रेलको लेखमा सुम्निमा उपन्यासलाई पूर्वीय काव्य सिद्धान्त अनुरूप रसविधानका आधारमा समीक्षा गरिएको छ भने खगेन्द्र घोडासैनीको लेख अछामी भाषाका रूपध्वनि प्रक्रियाको विश्लेषणमा केन्द्रित छ । त्यस्तै लक्ष्मीप्रसाद आचार्यको आलेखमा अन्तरक्रियात्मक शिक्षणप्रति शिक्षकका दृष्टिकोणको विश्लेषण गरिएको छ भने माया घिमिरेको लेखमा राजेश्वरी खण्डकाव्यलाई काव्यगुणका आधारमा विश्लेषण गरिएको छ ।